2021
DOI: 10.3389/fmed.2021.716816
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-Enriched Lactobacillus acidophilus Ameliorates Dextran Sulfate Sodium-Induced Chronic Colitis in Mice by Regulating Inflammatory Cytokines and Intestinal Microbiota

Abstract: Aim: To evaluate the effect of Selenium-enriched Lactobacillus acidophilus (Se-enriched L. acidophilus) on dextran sulfate sodium (DSS)-induced colitis in mice.Methods: Mice were randomly divided into four groups: a control group, a control + Se-enriched L. acidophilus group, a chronic colitis group, and a chronic colitis + Se-enriched L. acidophilus group (n = 10 each group). The mice were sacrificed on the 26th day. The disease activity index, survival rates, and histological injury score were determined. Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 54 publications
(65 reference statements)
4
19
0
Order By: Relevance
“…The relative abundance of Romoutsia also increased in DSS‐induced colitis in the study of Wu et al . (2021), which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The relative abundance of Romoutsia also increased in DSS‐induced colitis in the study of Wu et al . (2021), which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 94%
“…A study has shown that the relative abundance of Romboutsia is correlated with circulating inflammatory (IL-1b) and anxiety-like behaviour (Grant et al, 2021). The relative abundance of Romoutsia also increased in DSS-induced colitis in the study of Wu et al (2021), which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…As a probiotic, J‐15 mainly plays a role in regulating intestinal flora affected by kidney stone formation and helped restore the intestinal flora. This is pretty consistent with previous investigation on the changes in intestinal or fecal abundance of genus Lactobacillus after the administration of Lactobacillus strains in other disease models, 52,53 which might be due to the strain specificity, dosage, different animal models, and intestinal segments 54–56 . Our previous study on the microbial community composition of different intestinal segments after L .…”
Section: Discussionsupporting
confidence: 92%
“…This is pretty consistent with previous investigation on the changes in intestinal or fecal abundance of genus Lactobacillus after the administration of Lactobacillus strains in other disease models, 52,53 which might be due to the strain specificity, dosage, different animal models, and intestinal segments. [54][55][56] Our previous study on the microbial community composition of different intestinal segments after L. plantarum administration revealed that the amount of genus Lactobacillus varied widely among intestinal segments, 57 with the higher levels in the ileum and less in the cecum and colon. It suggests that L. plantarum significantly regulates the intestinal microflora of the ileum, rather than the cecum and colon.…”
Section: Discussionmentioning
confidence: 99%
“…As only one type of organic Se supplement is currently available, it is necessary to develop new organic Se products. Previous studies have shown that probiotics can be introduced to medium containing inorganic Se using the biotransformation method, which can convert inorganic Se into organic Se and form Se-enriched probiotics [14]. SeMet and SeCys are the main forms of Se in Se-enriched products.…”
Section: Introductionmentioning
confidence: 99%